Genomic Survey of Tyrosine Kinases Repertoire in Electrophorus electricus With an Emphasis on Evolutionary Conservation and Diversification. (May 2020) - Li, Ling; Liu, Dangyun; Liu, Ake; Li, Jingquan; Wang, Hui; Zhou, Jingqi
Tyrosine kinases (TKs) play key roles in the regulation of multicellularity in organisms and involved primarily in cell growth, differentiation, and cell-to-cell communication. Genome-wide characterization of TKs has been conducted in many metazoans; however, systematic information regarding this superfamily in Electrophorus electricus (electric eel) is still lacking. In this study, we identified 114 TK genes in the E electricus genome and investigated their evolution, molecular features, and domain architecture using phylogenetic profiling to gain a better understanding of their similarities and specificity. Our results suggested that the electric eel TK (EeTK) repertoire was shaped by whole-genome duplications (WGDs) and tandem duplication events. Compared with other vertebrate TKs, gene members in Jak, Src, and EGFR subfamily duplicated specifically, but with members lost in Eph, Axl, and Ack subfamily in electric eel. We also conducted an exhaustive survey of TK genes in genomic databases, identifying 1674 TK proteins in 31 representative species covering all the main metazoan lineages. Extensive evolutionary analysis indicated that TK repertoire in vertebrates tended to be remarkably conserved, but the gene members in each subfamily were very variable. Comparative expression profile analysis showed that electric organ tissues and muscle shared a similar pattern with specific highly expressed TKs (ie, epha7, musk, jak1, and pdgfra), suggesting that regulation of TKs might play an important role in specifying an electric organ identity from its muscle precursor. We further identified TK genes exhibiting tissue-specific expression patterns, indicating that members in TKs participated in subfunctionalization representing an evolutionary divergence required for the performance of different tissues. This work generates valuable information for further gene function analysis and identifying candidate TK genes reflecting their unique tissue-function specializations in electric eel.